Clinical and biological significance of isolated Y chromosome loss in myelodysplastic syndromes and chronic myelomonocytic leukemia. A report from the Spanish MDS Group. (December 2017) - Nomdedeu, Meritxell; Pereira, Arturo; Calvo, Xavier; Colomer, Joan; Sole, Francesc; Arias, Amparo; Gomez, Candida; Luño, Elisa; Cervera, Jose; Arnan, Montserrat; Pomares, Helena; Ramos, Fernando; et al.
Highlights: The clinical significance of chromosome Y loss (-Y) in MDS has been controversial. Our study analyzes the largest series of MDS with isolated −Y reported up to now. MDS patients with −Y are older and have less bone marrow blasts at diagnosis. A reduced risk of leukemic transformation has been observed in the −Y group. The reduced risk of leukemia does not translate into a survival advantage. Abstract: Isolate loss of chromosome Y (-Y) in myelodysplastic syndromes (MDS) is associated to a better outcome but it is also well described as an age-related phenomenon. In this study we aimed to analyze the prognostic impact of −Y in the context of the IPSS-R cytogenetic classification, evaluate the clinical significance of the percentage of metaphases with isolated −Y, and test whether finding −Y may predispose to over-diagnose MDS in patients with borderline morphological features. We evaluated 3581 male patients from the Spanish MDS Registry with a diagnosis of MDS or chronic myelomonocytic leukemia (CMML). −Y was identified in 177 patients (4.9%). Compared with the 2246 male patients with normal karyotype, −Y group showed a reduced risk of leukemic transformation that did not translate into a survival advantage. The overall survival and the risk of leukemic transformation were not influenced by the percentage of metaphases with −Y. The −Y group was not enriched in patients with minor morphologic traits of dysplasia, suggesting that the better outcome in the −Y group cannot be explained by enrichment in cases misdiagnosed as MDS. In conclusion, our results support the current recommendation of classifying patients with −Y within the very good risk category of the IPSS-R for MDS and rule out a selection bias as a possible explanation of this better outcome. An analysis of the molecular basis of MDS with isolated −Y would be of interest as it may provide a biological basis of protection against progression to acute leukemia.